The geochemical and fractionation study on toxic elements in road dust collected from the arterial roads in Kraków - Ewa Adamiec; Elżbieta Jarosz-Krzemińska; Robert Brzoza-Woch; Mateusz Rzeszutek; Jakub Bartyzel; Tomasz Pełech-Pilichowski; Janusz Zyśk (Archives of Environmental Protection, 2023)
Road dust should be considered as a secondary source of contamination in the environment, especially when re-suspended. In our study road dust samples were collected from 8 high-capacity urban roads in two districts of Kraków (Krowodrza and Nowa Huta). Total concentration of toxic elements, such as Cd, Cr, Cu, Mn, Zn, Co, Pb, Ni, Ba and Se were determined using ICP –MS ELAN 6100 Perkin Elmer. A fractionation study were performed using VI step sequential extraction, according to the modified method provided by Salomons and Fӧrstner. Appropriate quality control was ensured by using reagent blanks and analysing certified reference material BCR 723 and SRM 1848a. Concentration of metals in the road dust varied as follows [mg/kg]: Cd 1.02-1.78, Cr 34.4-90.3, Cu 65-224, Mn 232-760, Zn 261-365, Co 4.32-6.46, Pb 85.6-132, Ni 32.2-43.9, Ba 98.9-104 and Se 78.3-132. Degree of contamination of road dust from Nowa Huta was very high (Cdeg 54) and considerable for road dust from Krowodrza (Cdeg 25). Results revealed that road dust samples were heavily contaminated with Cd, Cu, Zn, Mn, Co, Pb, Ni, Ba and Se, in amounts exceeding multiple times geochemical background values. The chemical speciation study using VI step sequential extraction, followed by assessing risk assessment code (RAC) revealed that elements in road dust are mostly bound with mobile and easy bioavailable fractions such as carbonates and exchangeable cations, with the exception for Cr and Cu being mostly associated and fixed with residual and organic matter fraction.